Inconsistency in judges' legal considerations addressing special narcotics crimes - Muhamad Romdoni; Fathullah Fathullah; Mawarni Fatma; Zulfikri Darwis (The International Journal of Politics and Sociology Research, 2023)
The judge's legal considerations must be based on theories, jurisprudence, doctrine, trial evidence, and anything else that can clarify the case. Inconsistency in evaluating cases managed by judges in the same court for the same crime, however, can lead to inequity by imposing different sanctions. This study's objective is to examine the legal considerations judges take into account when resolving cases and issuing court decisions. This study employs a normative methodology with a comparative and statutory approach. The obtained data is then deductively processed and descriptively analyzed. The findings of this study indicate that the various judicial considerations contributed to the production of an unjust decision. This is evident from the decision number 273/Pid.Sus/2022/PN-Srg. This is due to the inconsistency of the judge's legal considerations, which leads to disparities in sentencing for narcotics-related offenses. This research shows that the regulations regarding narcotics in Indonesia are not optimal because judges as God's representatives on earth have not been able to provide the expected justice